Conceptual planning approach of low impact developments for combined water quality‐quantity control at an urban scale: A case study in Southern China. Issue 1 (29th September 2021) - Zhou, Qianqian; Luo, Jinhua; Qin, Zhao; Su, Jiongheng; Ren, Yi
Abstract: Managing urban water in many cities becomes more challenging under impacts of climate change and urbanization. Low impact development (LID) measures have been increasingly recognized and applied thanks to their capability of tackling multi‐dimensional water problems associated with both quantity and quality issues. Yet, in China limited attention has been paid to guide the planning strategy of LIDs in the preliminary stage, which often suffers from inadequate and imprecise data and information. In this study, an approach integrating a GIS‐based spatial evaluation model, a fuzzy comprehensive evaluation module and a multi‐objective optimization algorithm, is proposed to prioritize the spatial distribution of LIDs (i.e., type, placement, and extent) at the subcatchment scale in a case study in Southern China. By evaluating the trade‐offs among runoff reduction, pollution control, and economic investment, the synergies, and combination strategies of four types of LIDs are explored. Knowledge gained from this study is necessary and beneficial for water planners and practitioners to improve LID planning efficiency under constrained conditions.